Refining a questionnaire to assess breast cancer knowledge and barriers to screening in Kenya: Psychometric assessment of the BCAM. Issue 1 (December 2017) - Wachira, J.; Busakhala, A.; Chite, F.; Naanyu, V.; Kisuya, J.; Otieno, G.; Keter, A.; Mwangi, A.; Inui, T.
Abstract Background Our study objective was to determine the validity and reliability of the breast module of a cancer awareness measure (BCAM) among adult women in western Kenya. Methods The study was conducted between October and November 2012, following three breast cancer screening events. Purposive and systematic random sampling methods were used to identity 48 women for cognitive focus group discussions, and 1061 (594 who attended vs. 467 who did not attend screening events) for surveys, respectively. Face and psychometric validity of the BCAM survey was assessed using cognitive testing, factor analysis of survey data, and correlations. Internal reliability was assessed using Cronbach's alpha. Results Among survey participants, the overall median age was 34 (IQR: 26–44) years. Compared to those women who did not attend the screening events, women attendees were older (median: 35 vs. 32 years, p = 0.001) more often married (79% vs. 72%, p = 0.006), more educated (52% vs. 46% with more than an elementary level of education, p = 0.001), more unemployed (59% vs. 11%, p = 0.001), more likely to report doing breast self-examination (56% vs. 40%, p = 0.001) and more likely to report having felt a breast lump (16% vs. 7%, p = 0.001). For domain 1 on knowledge of breast cancer symptoms, one factor (three items) with Eigen value of 1.76 emerged for the group that did not attend screening, and 1.50 for the group that attended screening. For both groups two factors (factor 1 "internal influences" and factor 2 "external influences") emerged among domain 4 on barriers to screening, with varied item loadings and Eigen values. There were no statistically significant differences in the factor scores between attendees and non-attendees. There were significant associations between factor scores and other attributes of the surveyed population, including associations with occupation, transportation type, and training for and practice of breast self-examination. Cronbach's alpha showed an acceptable internal consistency. Conclusion Certain subpopulations are less likely than others to attend breast screening in Kenya. A survey measure of breast cancer knowledge and perceived barriers to screening shows promise for use in Kenya for characterizing clinical and community population beliefs, but needs adaptation for setting, language and culture.